Analisis Strategi Inovasi, Kreativitas, Pemasaran Digital, dan Sumber Daya Manusia pada UMKM DS Style Box - Dian Sasmitha; Yeremia Niaga Atlantika; Sabinus Beni; Benedhikta Kikky Vuspitasari (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: To describe innovation, creativity, marketing, and HR development strategies for improving DS Style Box's marketing performance, addressing stagnant sales caused by limited products, unappealing packaging, and inconsistent marketing. Methodology/approach:  This descriptive qualitative research collected data via observation, literature review, and interviews (3 key, 2 triangulation informants), analyzed through data reduction, display, and conclusion drawing. Findings:  Product innovation, design creativity, digital marketing, and HR competence are strategic factors. Main obstacles include limited product variety, unattractive packaging, and sub-optimal digital media utilization. Practical implications:  Businesses must develop trend-aligned products, improve packaging design, strengthen digital marketing, and utilize simple technologies (like AI) for customer service. Originality/value:  Offers a comprehensive solution to overcome sales stagnation by integrating creativity, HR competence, and technological adaptation in a specific case study.